Cooperative management practices how to influence the productive performance outcomes: Based on the analysis of China’s guangxi 94 farmers professional cooperatives - Ying-dong Zhao; Xin-chao Pan; Zi-lun Zhi; Chuan-yong Tang; Jie Dang; Kun-lin Bai (PLoS ONE, 2026)
Objectives Research on the key factors that influence the productive outcomes of farmer professional cooperatives (FPCs) is essential to develop targeted management approaches that promote sustainable growth. This study investigates how cooperative management practices influence productive performance outcomes through an analysis of 94 FPCs in Guangxi, China. Methods Employing cluster analysis, Ordinary Least Squares (OLS) regression, and mediation effect tests, the research categorizes management practices into five typologies (Comprehensive High-Efficiency, Collaboration-Deficient, Monitoring-Deficient, Planning-Deficient, Holistically Deficient) and links these to five distinct performance outcomes (Profitable Outreach High-Efficiency, Loss-Making Insular Low-Efficiency, etc.). Results Results reveal that management practices critically determine performance outcomes types. Regression analysis highlights planning practices significantly influenced profitability, while investment practices positively impacted employment generation. Internal governance practices were strongly associated with institutional compliance, and external collaboration practices had a significant effect on technology dissemination and community reputation.Monitoring practices, while not directly impacting performance outcomes, were found to enhance them through management practices and mechanisms. Key behavioral indicators—revenue planning, capital investment, staff capacity, and role optimization—emerge as primary levers for performance optimization. Conclusion This study underscore the critical role of management practices in shaping the performance of FPCs, suggestions include emphasizing efficient planning, investing in personnel training, and establishing dynamic adjustment mechanisms to ensure sustainable development. These findings provide empirical insights for optimizing rural collective governance and informing evidence-based policy interventions in developing agricultural economies.